2021
DOI: 10.1530/eje-21-0144
|View full text |Cite
|
Sign up to set email alerts
|

Defective insulin maturation in patients with type 2 diabetes

Abstract: Objective: Progressive beta cell dysfunction is a hallmark of type 2 diabetes (T2D). Increasing evidence indicates that over-stimulating proinsulin synthesis causes proinsulin misfolding and impairs insulin maturation and storage in db/db mice. However, defective insulin maturation in patients with T2D remains unknown. Methods: We examined intra-islet and intra-cellular distributions of proinsulin and insulin and proinsulin to insulin ratio in the islets of patients with T2D. The expression of transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Misfolded proinsulin is recognized by ER quality control machinery, preventing its export from the ER to the Golgi complex ( 14 , 16 ). We therefore examined localization of proinsulin and found that, consistent with our previous findings ( 14 , 33 ), proinsulin in wild-type β cells was mostly concentrated in the juxtanuclear region (suggesting successful proinsulin trafficking from the ER to the Golgi complex), whereas in IER3IP1-βKO β cells, proinsulin was more diffusely distributed throughout the cytoplasm (additionally, some proinsulin-positive cells lost detectable insulin, i.e., Pro + Ins − ), suggesting defective anterograde trafficking of proinsulin ( Fig. 4 G and H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Misfolded proinsulin is recognized by ER quality control machinery, preventing its export from the ER to the Golgi complex ( 14 , 16 ). We therefore examined localization of proinsulin and found that, consistent with our previous findings ( 14 , 33 ), proinsulin in wild-type β cells was mostly concentrated in the juxtanuclear region (suggesting successful proinsulin trafficking from the ER to the Golgi complex), whereas in IER3IP1-βKO β cells, proinsulin was more diffusely distributed throughout the cytoplasm (additionally, some proinsulin-positive cells lost detectable insulin, i.e., Pro + Ins − ), suggesting defective anterograde trafficking of proinsulin ( Fig. 4 G and H ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 70 INS gene mutations associated with diabetes, the majority impair proinsulin oxidative folding with defective export from the endoplasmic reticulum (ER) ( 8 10 ) while also interacting (and impairing trafficking) of the coexpressed wild-type INS gene product, thereby decreasing insulin production ( 11 13 ). Proinsulin misfolding with defective formation and storage of mature insulin may also contribute to the development and progression of T2D ( 14 16 ).…”
mentioning
confidence: 99%
“…Immunofluorescence of the pancreatic β cells was performed as previously described [ 30 ]. Briefly, pancreatic β cells (2 × 10 4 ) were cultured in 24-well culture plates, fixed with 4% paraformaldehyde for 30 min, washed twice with PBS, and then permeabilized with methanol for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that defective COPII dependent cargo export could be one of the underlying causes for the major beta cell defects in diabetes including impaired proinsulin maturation, loss of insulin content, abnormal insulin granule morphology, chronic ER stress and beta cell apoptosis in diabetes (1,4,73,103). In fact, defective insulin maturation with increased ER localization of proinsulin was reported in the beta cells of type 2 diabetes patients (104). It will be of importance to determine if ERES organization or COPII coat assembly is altered in human diabetic islets.…”
Section: Defective Er Export In Beta Cell Dysfunction and Diabetesmentioning
confidence: 99%